Billions of entrepreneurs : - Khanna, Tarun (Harvard Business, 2011)
Billions of Entrepreneurs is an elegantly written book that mixes on-the-ground stories with thorough research to show how Chinese and Indian entrepreneurs are creating change through new business models, and bringing hope to countless people across the globe.